GERMAN INSTITUTIONS IN VALPARAISO 1850 -1930: A FORM OF DEFENSE OF CULTURAL IDENTITY - Estrada Turra, Baldomero (Revista de Historia Social y de las Mentalidades, 2024)
It analyzes the different institutions created by the German collectivity of Valparaiso, during the period 1850-1930, in order to detect the functions fulfilled regarding these organisms stimulated German identity preservation or, conversely, facilitated integration belonging to the host society. Particularly striking is the large number of institutions created and the strong relationship between these measures and the use of financial and trading organizations of Germanic origin. On the other hand, are perceived class features in many of the associations, especially in the field of sociability, thus meeting places are different. It also receives a different level of participation of the members of the community as a result of the social position to which they belong, so that the elite assumed the leadership and financial support of associations and other sectors, they use of the services delivered canceling those shares as partners.